Assessment of radiation and heavy metals risk due to the dietary intake of marine fishes (Rastrelliger kanagurta) from the straits of Malacca - Khandaker, Mayeen Uddin; Asaduzzaman, Khandaker; Nawi, Saiful Mazwan; Usman, A. A.; Amin, Y; Daar, E.; Bradley, D.A.; Ahmed, H.; Okhunov, Abdurahim (The Public Library of Science (PLoS), 2015)
The environment of the Straits of Malacca receives pollution as a result of various industrial and anthropogenic sources, making systematic studies crucial in determining the prevailing water quality. Present study concerns concentrations of natural radionuclides and heavy metals in marine fish (Rastrelliger kanagurta) collected from the Straits of Malacca, since aquatic stock form an important source of the daily diet of the surrouding populace. Assessment was made of the concentrations of key indicator radionuclides (226Ra, 232Th, 40K) and heavy metals (As, Mn, Fe, Cr, Ni, Zn, Cu, Co, Sr, Al, Hg and Pb) together with various radiation indices linked to the consumption of seafish. The annual effective dose for all detected radionuclides for all study locations has been found to be within UNSCEAR acceptable limits as has the associated life-time cancer risk. The overall contamination of the sampled fish from heavy metals was also found to be within limits of tolerance.